(untitled) (Journal of Academic Research, 2025)
This study explored the gap between theory and classroom practice. It investigated English graduates perspectives of the challenges they faced when they attempted to carry out theoretical knowledge they learned in the university study. The study aimed to provide the key factors that contributed to the gap between theory and practice in teaching English. Moreover, it investigated the role of syllabus design in bridging this gap between theoretical courses in Faculty of Education and the practical application in public schools. A descriptive research was employed to gather insights into the challenges English graduates faced in their teaching. The participants of the study were 36 of English graduates studied in Faculty of Education. Findings revealed that there was a gap between theoretical knowledge and practical use. Moreover, the study found out that the basic key factors that contributed to challenges that prevented graduates to apply theoretical knowledge were students’ low proficiency, lack of school supplies, test-oriented students, lack of training workshops, managing mixed- ability students and large class sizes. Furthermore, it concluded that the syllabus found in public school was designed to suit innovative English teaching methodology.